Vibrotactile perception sensitivity and its relation to hand-arm vibration exposure - Lundström, R; Nilsson, T; Burström, L; Hagberg, M (Central European journal of public health, 1995)
Vibrotactile perception thresholds (VPT) at seven test frequencies (8-500 Hz) have been measured and evaluated among 170 male employees at a heavy engineering production workshop, 125 of them were at present, or in the past, exposed to hand-arm vibration. All participants were examined by a physician and none had symptoms of diseases or were exposed to other factors known to cause sensory neuropathies. VPTs [for the three lowest (8-32 Hz; non-Pacinian), for the four highest (63-500 Hz; Pacinian) and for all test frequencies together] and a sensitivity index (SI) has been individually graded in four (normal, slightly deteriorated, deteriorated and seriously deteriorated) and two (normal, abnormal) stages, respectively, and put in relation to individual exposure of vibration. The results do not show any clear relationship on an individual basis between vibration exposure and degraded vibrotactile perception. On a group basis, however, there is a clear tendency towards detoriorated VPTs when the study group is divided in exposure categories. The detorioration is most pronounced in the frequency range mediated by Pacinian corpuscles. In this range an approximately four-fold increase of relative risk for elevated VPT for those in the highest exposure category was observed compared to the non-exposed group. Corresponding relative risk estimate for SI is about 6. Therefore, the results suggest an existence of an exposure-response relationship.
Keywords: Vibration; Time Factors; mužské pohlaví; Fingers; Adult; prsty ruky; Models, Biological; Touch; Occupational Exposure; Humans; Cumulative Trauma Disorders; Differential Threshold; pracovní expozice; časové faktory; biologické modely; vibrace; Risk; poranění z opakovaného přetěžování; riziko; diferenční práh; dospělí; lidé; Male; hmat